2001
DOI: 10.1088/0022-3727/34/23/305
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of fast electrons and heavy particles in the CDS of nitrogen dc glow discharge

Abstract: The characteristics of fast electrons (e-) and heavy particles (N2+, N+, N2f, Nf) in the cathode dark space (CDS) of nitrogen dc glow discharge are simultaneously studied by Monte Carlo simulation. The calculated energy and angular distributions of these particles at different positions from the cathode provide a clear picture of their transport behaviours within the CDS. The density and mean energy of these particles indicate that the electrons and the atomic ions (N+) are the main high-energy species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…A Bogaerts et al have simulated capacitively coupled radio-frequency (ccrf) discharge in methane with a fluid model and have shown that calculated time-averaged CH + 5 ion density decreases with increasing flow rate [9] . The distribution of the mean density of N + ions is similar to that of N + 2 , and the density of N + is about six times less than N + 2 by our calculation, the reason for which can be found in our previous work [12] . In Fig.…”
Section: The Radial and Axial Electric Fieldsupporting
confidence: 80%
“…A Bogaerts et al have simulated capacitively coupled radio-frequency (ccrf) discharge in methane with a fluid model and have shown that calculated time-averaged CH + 5 ion density decreases with increasing flow rate [9] . The distribution of the mean density of N + ions is similar to that of N + 2 , and the density of N + is about six times less than N + 2 by our calculation, the reason for which can be found in our previous work [12] . In Fig.…”
Section: The Radial and Axial Electric Fieldsupporting
confidence: 80%
“…其中,  (eV)为带电粒子能量,  (m 2 )为带电粒子的碰撞截面, 由 决定 [28] , N 0 (m -3 ) 为背景 Ar 原子的数密度。模型中设定气压 p 为 0.5 Pa,背景温度 T 为 300 K,则 忽略离子半径与原子半径的差异 [31] ,因此 Ar + 和 Ar 的碰撞截面 Ar Ar    由公式( 9)…”
Section: 仿真模型的构建unclassified
“…2 ) in the hollow cathode cavity are equal and uniformly distributed; the densities of atomic ions (N + ) and molecular ions (N + 2 ) are assumed to be roughly 1:5 [15] . The initial velocity of the particles is sampled from a Maxwellian velocity distribution at an average electron temperature of 2 eV and ion temperature of 0.0625 eV (300 K).…”
Section: Description Of the Modelmentioning
confidence: 99%